Hubungan Antara Konsep Diri Dengan Intensi Menyontek - ARIFAH, ENIS RACHMAWATI, Taufik Kasturi, S.Psi., M.Si., Ph.D (2016)
Intension of cheating is the intention or desire to get answers during the test to obtain the value of unlawfully using the information from the outside, based on the person's attitudes and beliefs as well as attitudes and beliefs of others that influence the behavior of cheating. Various levels ranging from elementary school through college, a person with positive academic self-concept have better academic achievement and establish open communication with teachers and students so as to create the active participation of both the teaching and learning activities. The purpose of this study was to determine the relationship between self-concept with the intention of cheating, the level of self-concept, the level of intention to cheat and effective contribution of self-concept to the intention of cheating. The hypothesis is there is a negative relationship between self-concept with the intention of cheating. This research method is quantitative with the subject 184 N 04 Surakarta high school students by means of cluster random sampling. The data in this study is the product moment correlation test. Based on the analysis of data obtained coefficient (r) of -3.44, p = 0.000 <0.01, which means there is a significant negative relationship between self-concept with the intention of cheating. Based on the results of analysis variables self-concept has the empirical mean (RE) amounted to 102.81 and the mean hypothetical (RH) of 65, which means self-concept on the subject is very high. While the intention of cheating variables have the empirical mean (RE) of 79.54 and the mean hypothetical (RH) of 82.5, which means self-concept in subjects classified as moderate. The effective contribution of self-concept to the intention of cheating by 11.8%, therefore there are still 88.2% of other variables that contribute to the intention of cheating Keywords: self-concept, intention to cheat, high school students